2002
DOI: 10.1248/bpb.25.422
|View full text |Cite
|
Sign up to set email alerts
|

Development of Radioimmunoassay for Measurement of Serum Digoxin in Digitalized Patients Using Novel Anti-digoxin Antiserum.

Abstract: Digoxin is the most widely used cardiac glycoside for the treatment of congestive heart failure and atrial fibrillation. Digoxin is known to be converted metabolically to digoxigenin bis-digitoxoside, digoxigenin mono-digitoxoside and digoxigenin by cleavage of the sugar moiety. 1,2) In addition, it is metabolized to dihydrodigoxin by reduction of the double bond in the lactone ring.3)The analysis of digoxin in biological fluids can be performed by immunoassays. The antisera used for these immunoassays are pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Several methods for the determination of DG in bio-matrix also have been reported, including immunoassay techniques [17,18], HPLC methods [19,20] and LC-MS/MS methods [21,22]. However, to our knowledge, no analytical method has been reported that is able to simultaneously determine MDZ, 1 -OHMDZ and DG in bio-matrix after co-administration of MDZ and DG.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for the determination of DG in bio-matrix also have been reported, including immunoassay techniques [17,18], HPLC methods [19,20] and LC-MS/MS methods [21,22]. However, to our knowledge, no analytical method has been reported that is able to simultaneously determine MDZ, 1 -OHMDZ and DG in bio-matrix after co-administration of MDZ and DG.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, therapeutic drug monitoring for digoxin incorporates a wide variety of immunoassay techniques including radio immunoassay (Ikeda et al, 2002), microparticle enzyme immunoassay (Azzazy et al, 1997), turbidimetric immunoassay (Datta and Dasgupta, 2004), fluorescence polarization immunoassay (Ijiri et al, 2004) and enzyme-linked chemiluminesent immunosorbent assays (Dasgupta et al, 2006). These techniques depend on the binding specificity of an antibody to digoxin to produce a radioactive, chemiluminescent, turbidimetric or fluorescent signal.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported the preparation and antigenic properties of digitoxin-bovine serum albumin (BSA), Dx-BSA, and h-methyldigoxin-BSA conjugates linked at the digitoxose C-3V and C-3W positions using radio immunoassay (RIA) or enzyme immunoassay (EIA) (Fujii et al, 1991(Fujii et al, , 1994Ikeda and Fujii, 2000;Ikeda et al, 2001Ikeda et al, , 2002Higashi et al, 2002). Our previous results suggested that antisera to these conjugates linked at the digitoxose C-3V position showed higher specificity to metabolites, while a commercially available anti-digitoxin and Dx antisera exhibited remarkable cross-reactivities.…”
Section: Introductionmentioning
confidence: 99%